2005
DOI: 10.1086/429238
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind Clinical Trial of Topical Imiquimod 5% with Parenteral Meglumine Antimoniate in the Treatment of Cutaneous Leishmaniasis in Peru

Abstract: Combined antimony plus imiquimod treatment was well tolerated, accelerated healing of lesions, and improved scar quality. This therapy may have particular advantages for subjects with facial lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 26 publications
2
84
2
2
Order By: Relevance
“…In the study of Miranda-Verastegui et al (2005), which was conducted in the endemic regions of the Peruvian Andes and tropical forest, they included 40 patients which were infected by L. peruviana and L. braziliensis. However, the side effects that were reported in the group treated with imiquimod, were erythema, edema, itching, burning and pain (Almeida and Santos 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Miranda-Verastegui et al (2005), which was conducted in the endemic regions of the Peruvian Andes and tropical forest, they included 40 patients which were infected by L. peruviana and L. braziliensis. However, the side effects that were reported in the group treated with imiquimod, were erythema, edema, itching, burning and pain (Almeida and Santos 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole was not found effective in primary treatment of New world mucocutaneous leishmaniasis in a small controlled clinical trial [19], although anecdotal evidence suggests that this drug may have some utility in the treatment of New World cutaneous leishmaniasis [20,21], particularly in consolidation or maintenance therapy, as seen in our case. Local, topical treatment with photodynamic therapy [22], paromomcym [23], and the immune stimulator imiquimod [24][25][26] have also been shown to be effective treatments for L. (Vianna) braziliensis-related New World cutaneous leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled trial of the new world CL, it was shown that in all patients treated with imiquimod alone, the disease was relapsed after treatment discontinuation but all patients treated with combination of imiquimod and MG were cured (Arevalo et al, 2007). Similar studies in Peruvian patients revealed the same results with small scar tissue, so it was proposed to recommend for the facial lesions (Miranda-Verastegui et al, 2005). Other reports in old world cutaneous leishmaniasis confirmed treatment failure when topical imiquimod cream used alone and its additive effect when used in association with antimony compounds (Arevalo et al, 2001;Seeberger et al, 2003).…”
Section: Immunomodulator As An Adjuvant Imiquimodmentioning
confidence: 95%